2019
DOI: 10.4103/jisp.jisp_512_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of early periodontal disease among adolescents

Abstract: Background: Periodic estimation of periodontal disease burden is essential for formulating new treatment strategies, for evaluating preventive strategies, and for framing of new policies. The previous national-level survey among adolescents was held 15 years ago. The objective of this study was to estimate the prevalence of periodontal disease among older adolescent students and to analyze its predictors as part of an oral health assessment survey conducted in Kerala. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…In late adolescents, although severe periodontitis is quite rare, studies have reported that gingival inflammation (gingivitis) is often observed [17,18]. However, as the association between periodontal diseases and systemic diseases has not been adequately elucidated in late adolescents, we focused on the relationship between gingival health status and common systemic diseases in late adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In late adolescents, although severe periodontitis is quite rare, studies have reported that gingival inflammation (gingivitis) is often observed [17,18]. However, as the association between periodontal diseases and systemic diseases has not been adequately elucidated in late adolescents, we focused on the relationship between gingival health status and common systemic diseases in late adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the same has not been well investigated in younger people, and, therefore, the relationship has yet not been clarified in late adolescence. Though severe periodontitis accompanied by tooth mobility is quite rare in late adolescence, studies have reported that gingivitis (which can cause gum bleeding) is occasionally observed at that age [17,18]. Considering this situation, we conducted the present study to investigate the relationship between gum bleeding and the following common systemic diseases, which are often observed in late adolescents: allergic diseases/disorders (pollinosis, food/drug allergy, inhaled antigen allergy, and atopic dermatitis), otorhinolaryngologic diseases (allergic rhinitis, otitis media/externa, and sinusitis), and respiratory disorders (infectious diseases, pneumothorax/mediastinal emphysema, and asthma/cough-variant asthma).…”
Section: Introductionmentioning
confidence: 99%
“…Cases of gingival bleeding in puberty have been widely reported [30]. Our results showed that the incidence of bleeding gums increased with age, which might be related to prolonged exposure to risk factors and inflammation associated with hormonal changes [31].…”
Section: Discussionmentioning
confidence: 48%
“…Yet, oral diseases are one of the major non-communicable diseases affecting over 3.5 billion people (Bernabe et al, 2020). About 10% of the global population is affected by severe periodontal (gum) disease, which often results in tooth loss (WHO, 2021, Baiju et al, 2019). Besides, there are 530 million cases of dental caries/tooth decay/cavities among children, the majority of whom live in low and middle-income countries (LMCs), where provision of dental services is limited (WHO, 2021, Batwala et al, 2007).…”
Section: Introductionmentioning
confidence: 99%